Synthesis of the aglycon of aspafiliosides E and F based on cascade reactions. Issue 9 (18th December 2015) - Wu, Jing-Jing; Shi, Yong; Tian, Wei-Sheng
Abstract : Herein, we describe an efficient synthesis of C17α-OH-tigogenin, which is the aglycon of aspafiliosides E and F. The synthesis features three cascade processes, which involve the iodo-lactonization of furostan-26-acid, a cascade hydrolysis/intramolecular SN 2 process, and a cascade intramolecular redox-ketalization process. Abstract : A synthesis of C17α-OH-tigogenin, the aglycon of aspafiliosides E and F, is described. The main features of the synthesis are three cascade processes, which involve the iodo-lactonization of furostan-26-acid to open ring E, a cascade hydrolysis/intramolecular SN 2 process to close ring E, and a cascade intramolecular redox-ketalization process to close ring F. This synthesis would enrich the strategies used for the manipulation of spiroketals in steroidal sapogenins and other substrates.